Improving Students’ Skills in Writing Descriptive Texts by Using Digital Photographs - Khadijah Maming; Ali Wira Rahman; Amir Patintingan; Devy Anggraini (Surakarta English and Literature Journal, 2023)
In English Learning Teaching (ELT), digital photographs are considered a compelling visual medium to help students write English texts. A writing skill is a capacity to convert ideas into complete, comprehensive and understandable sentences that may be used to convey those ideas to the reader effectively. The purpose of this research is to find out whether using digital photographs can improve students’ skills in writing descriptive texts or not. The researchers used a descriptive quantitative pre-experimental method by applying digital pictures to teach writing descriptive text. The sample of this research consists of thirty students at SMP Negeri 1 Pangsid, South Sulawesi. The result shows that students’ writing skills increased by using digital photographs. The results are indicated by the mean value of the pretest (44,73) and the posttest (82,93). After calculating the t-test, the researchers found that the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. Using digital photographs as a teaching and learning medium can improve students’ skills n writing descriptive texts. In other words, this medium eases the students in constructing their ideas through descriptive essays.